Acute respiratory distress syndrome due to SARS-CoV-2 and Influenza A co-infection in an Italian patient: Mini-review of the literature - D’Abramo, Alessandra (Int J Infect Dis, 2020)
A case of acute respiratory distress syndrome due to SARS-CoV-2 and Influenza A co-infection and a mini-review of the literature is reported. Even in COVID-19 epidemics, the early identification of concurrent respiratory pathogens is important to improve etiological diagnosis, preventive measures and patients’ clinical management and outcome.